The Archetypal Character of Eve: A Comparative Overview of Modern Czech, French and Canadian Literatures - Střelec, Karel (Poznańskie Studia Slawistyczne, 2024)
There are very few archetypal characters being more important for European cultural tradition than the Biblical first woman – Eve. As evidenced by literary onomastic research, the very use of semantically loaded first names implies intertextual connectedness, fulfilling – in most cases – associative and symbolic functions. This reference to archetypal stories and heroes makes it possible to create a multitude of new semantic layers, but it also serves to keep their original sense in cultural and collective memory. In our contribution, we seek comparative analysis and interpretation of selected characters, bearing the name of Eve, in modern French, Canadian and Czech literatures. The study focuses on variants, shifts, and similarities that, to varying extents, refer to the first Biblical woman. Throughout both the national literatures, we observe forms of the pretext−posttext relation and concrete onymic functions of the name of Eve in the time span from the close of the 19th century to the present day.